HUBUNGAN KETAHANAN PANGAN KELUARGA DENGAN STATUS GIZI KELUARGA BURUH KAYU DI KAMPUNG KOTALINTANG KECAMATAN KOTA KUALA SIMPANG KABUPATEN ACEH TAMIANG PROVINSI ACEH TAHUN 2014 - Diza Fathamira Hamzah, SKM., M.Kes (JUMANTIK (Jurnal Ilmiah Penelitian Kesehatan), 2016)
ABSTRACT  Lack of income will lead family’s inability in providing nutritious food for all family members. The condition is closely related to the household food security. Indirectly, household food security is related to family nutritional status.The research used observational method with cross-sectional design which aims to know the correlation between household food security and nutritional status of wood worker’s family. The population were whole wood worker’s family and 83 of them were used as the study sample obtained by simple random sampling method. The correlation between household food security and the family nutritional status was analyzed by using Fisher’s Exact Test with confidence level of 95%. The result showed most families are sensitive household food security (61,4%) and the family nutritional status classified as good (80,7%). Fisher Exact Test’s indicated no significant correlation between household food security and the nutritional status of wood worker’s family (p=0,076). This research indicated the household food expenditure percentage as the indicator of household food security was not sensitive to predict the nutritional status of low income family.It is recommended  for local government attention is required  to achieve the sustainable household food security for whole society wood worker’s family. Beside, it is important to improve the  nutrition and health promotion effort by health workers and community leaders in order to achieve and mantain the good family nutritional status.  Keywords : Household Food Security, Nutritional Status, Wood Worker